An Analysis of the Violation of Maxims in “Just Friends” Webtoon by CL Nuna - nisa, Khoirunnisa' Hamidah; Sabat, Yuliyanto; Aisyah , Siti (Universitas Nusantara PGRI Kediri, 2023)
This research aims to analyze the violating of maxims on the conversation in the webtoon Just Friends by CL Nuna and determine which flouting of the maxims is the most dominant. This research uses a descriptive qualitative method because it explains a lot about violations of maxims. There are 8 data from 1 to 8 episodes that have been analyzed. The process of analyzing uses the theory of Grice which suggests four cooperative principles. Namely manner, relations, quantity and quality. Hasil analisis researchers found many violating from maxims of quantity with a frequency of 3 data and a percentage of 37%. 1 violation of maxims in data quality with 13%. 2 data in violation of maxims relations and 2 data in violation of maxims manner which amounted to 25% percentages.